2018
DOI: 10.23736/s1973-9087.17.04815-8
|View full text |Cite
|
Sign up to set email alerts
|

Technologically-advanced assessment of upper-limb spasticity: a pilot study

Abstract: A copyedited and fully formatted version will be made available soon. The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…Furthermore, the study by Bustren et al (2017) included only individuals capable of performing the drinking task with both upper limbs, whereas our study on the ipsilesional upper limb included individuals who were unable to complete the task with the contralesional upper limb, which may explain the discrepancy in results. Posteraro et al (2018) have reported increased activation of sensory-motor areas in the contralesional hemisphere in individuals during the early stage after a stroke. This finding may provide an explanation for the results observed in our study during the early phase of recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study by Bustren et al (2017) included only individuals capable of performing the drinking task with both upper limbs, whereas our study on the ipsilesional upper limb included individuals who were unable to complete the task with the contralesional upper limb, which may explain the discrepancy in results. Posteraro et al (2018) have reported increased activation of sensory-motor areas in the contralesional hemisphere in individuals during the early stage after a stroke. This finding may provide an explanation for the results observed in our study during the early phase of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of ipsilesional upper limb reaching movements after stroke has been described as similar to those in individuals without stroke for up to 3–4 months after the injury (Bustren et al, 2017; Metrot et al, 2013). However, reduced movement smoothness (Metrot et al, 2013; Posteraro et al, 2018) and increased latency for movement onset and duration persist into the chronic phase (de Paiva Silva et al, 2018). The impairment level of the paretic side seems to affect the performance of the ipsilesional upper limb in the chronic phase (Bustren et al, 2017; de Paiva Silva et al, 2018; Pallant, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Participants with spasticity after UMN injury (stroke, CP, MS, SCI, etc.) were included ( Posteraro et al, 2018 ). The spasticity was defined that Modified Ashworth Scale (MAS) was greater than 0 ( Balci, 2018 ), the Brunnstrom stage was greater than I or author reported spasticity.…”
Section: Methodsmentioning
confidence: 99%
“…The spasticity refers to abnormal increase of muscle tone, which is associated with upper motor neuron (UMN) injury occurring in stroke, spinal cord injury (SCI), cerebral palsy (CP), multiple sclerosis (MS), and others ( Dietz and Sinkjaer, 2012 ; Posteraro et al, 2018 ). After UMN injury, owing to loss of supraspinal inhibition, bulbospinal pathways become hyperexcitable, the presynaptic inhibition of muscle spindle afferents reduce and muscular tone increase ( Li S. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, even the two most popular scales based on manual tests of resistance to stretch, namely the Modified Ashworth Scale (MAS) and Modified Tardieu Scale (MTS), have been reported to have poor reliability and validity [5]; moreover, both scales are operator-dependent, time-consuming to apply and have scarce sensitivity to progressive improvements during treatment, which is a crucial feature for rational, assessment-driven rehabilitation [6]. The alternative to clinical scales is the use of electromechanical or robotic systems [7]- [9], to provide precisely controlled stretches, integrated with the concurrent analysis of the short and long latency components of the stretch reflex [10]. In addition to the general shortcoming of clinical scales mentioned above, a recent study has demonstrated that such evaluations (particularly in regards to the MAS evaluation) do not correlate with neuromechanical measurements of spasticity [11].…”
Section: Introductionmentioning
confidence: 99%